Radiological and Surgery Considerations and Alternatives in Total Temporomandibular Joint Replacement in Gorlin-Goltz Syndrome - Kamil Nelke; Klaudiusz Łuczak; Maciej Janeczek; Agata Małyszek; Piotr Kuropka; Maciej Dobrzyński (Diagnostics)
Gorlin-Goltz syndrome (GGS) is also known as Nevoid basal cell carcinoma syndrome (NBCCS). In the most common manifestation, GGS is diagnosed based on multiple cysts in the jaw bones, namely OKCs (odontogenic keratocysts). Other features might include major and minor clinical and radiological criteria to confirm this syndrome. Quite commonly, BCCs (basal cell carcinomas), bifid ribs, palmar and plantar pits, and ectopic calcification of the falx cerebri can be found in the majority of patients. Currently, the mutation of the PTCH1 gene seems to be responsible for GGS occurrence, while the male-to-female ratio is 1:1. The following radiological study based on OPGs and CBCT confirmed multiple cystic lesions in jaw bones, confirmed to be OKCs in the histopathological evaluation with an occurrence of numerous skin BCC lesions. In cases of most oral OKC cystic lesions, either surgical removal, curettage, or enucleation with or without any bone grafting can be used with a good amount of success. Rarely, some stable bone osteosynthesis procedures have to be carried out to avoid pathological bone fractures after cyst removal. A special consideration should include the temporomandibular joint. TMJ surgery and the replacement of the joint with an alloplastic material can be performed to improve biting, chewing, proper mouth opening, and maintain good patient occlusion. The authors want to present how effective and simple a standard dental panoramic radiograph combined with CBCT is and how it is suitable for GGS detection. They also want to underline how a standard TMJ prosthesis can be used as an alternative to a custom-made prosthesis.